Salvage surgery for local failures after stereotactic ablative radiotherapy for early stage non-small cell lung cancer. Issue 1 (December 2016) - Verstegen, Naomi; Maat, Alexander; Lagerwaard, Frank; Paul, Marinus; Versteegh, Michel; Joosten, Joris; Lastdrager, Willem; Smit, Egbert; Slotman, Ben; Nuyttens, Joost; Senan, Suresh
Abstract Introduction The literature on surgical salvage, i.e. lung resections in patients who develop a local recurrence following stereotactic ablative radiotherapy (SABR), is limited. We describe our experience with salvage surgery in nine patients who developed a local recurrence following SABR for early stage non-small cell lung cancer (NSCLC). Methods Patients who underwent surgical salvage for a local recurrence following SABR for NSCLC were identified from two Dutch institutional databases. Complications were scored using the Dindo-Clavien-classification. Results Nine patients who underwent surgery for a local recurrence were identified. Median time to local recurrence was 22 months. Recurrences were diagnosed with CT- and/or 18FDG-PET-imaging, with four patients also having a pre-surgical pathological diagnosis. Extensive adhesions were observed during two resections, requiring conversion from a thoracoscopic procedure to thoracotomy during one of these procedures. Three patients experienced complications post-surgery; grade 2 (N = 2) and grade 3a (N = 1), respectively. All resection specimens showed viable tumor cells. Median length of hospital stay was 8 days (range 5–15 days) and 30-day mortality was 0 %. Lymph node dissection revealed mediastinal metastases in 3 patients, all of whom received adjuvant therapy. Conclusions Our experience with nine surgical procedures for local recurrences post-SABR revealed two grade IIIa complications, and a 30-day mortality of 0 %, suggesting that salvage surgery can be safely performed after SABR.